Academic stress through salivary biomarkers: A multivariate exploration of cortisol, IL-1β, CRP, and IgA levels with sex-specific insights - Rodrigo Castillo-Klagges; Camila Pezo-Sáez; Luis Aguila; Verónica Pantoja; Favián Treulen (PLoS ONE, 2026)
Academic stress activates physiological responses mediated by the sympathetic-adrenal-medullary axis and the hypothalamic-pituitary-adrenal axis, leading to the release of biomarkers such as cortisol and proinflammatory cytokines. While stress physiology has been extensively studied in clinical populations, few studies have systematically examined the association between academic stress and multiple salivary biomarkers in undergraduates, particularly with attention to sex differences. This cross-sectional study investigated the relationship between self-reported academic stress survey measured via the SISCO inventory and four salivary biomarkers of cellular inflammation: cortisol, interleukin-1β, C-reactive protein, and immunoglobulin A in 81 undergraduates (53 females, 28 males). Biomarker levels were quantified using ELISA, and data were analyzed via multivariate approaches (ANOVA, Pearson correlations, and linear regression modeling). Participants were categorized as low (37%), moderate (35%), and high (28%) stress levels based on SISCO scores. Although no statistically significant associations were found between SISCO scores and individual biomarkers, multivariate analysis revealed a predictive model (R² = 0.14) combining all four biomarkers, with stress level predictions within ±20% of observed values. Males in the high-stress score showed lower cortisol trends but higher proinflammatory markers compared to females, suggesting divergent physiological stress responses by sex. These findings provide preliminary evidence for sex-differential association in self-reported academic stress with biological markers of inflammation, highlighting the potential of biomarker panels rather than single markers to capture the complexity of academic stress. In addition, this study establishes a methodological framework for combining psychometric tools with multi-biomarker analyses in stress research, addressing a critical gap in the literature on academic stress physiology.